Works of art on paper: history, conservation, and recommendations - Lennartson, Kari, author (Colorado State University. Libraries, 2002)
As an artist excited about the possibilities of painting on paper, I am increasingly aware of the importance of conservational concerns, which surround my own artwork. Although it is the work of art conservators to preserve existing works of art, it is the responsibility of the artist to be aware of conservation issues in regards to their chosen medium, and thereby to take steps to improve the quality of their own artwork. An informed artist will seek to educate themselves, not only about the history of their given medium, but also about the properties of the materials utilized in the process. The process of researching this essay involved extensive library and internet research, as well as informal, yet informative discussions with professors and colleagues. The research laid out in this essay has provided me with a valuable learning experience, which has already informed my own artwork, in terms of choice of materials and artwork storage. It is my sincere desire to share this research with my colleagues, and to pass along my newfound knowledge to future students who exhibit similar interests in working on paper. "Go on working, freely and furiously and you will make progress." -Paul Gauguin.
Studio research.
MFA candidate.
2002 Fall.
Keywords: art on paper; Art -- Conservation and restoration